2021
DOI: 10.6023/cjoc202103011
|View full text |Cite
|
Sign up to set email alerts
|

Tetraphenylethylene-Based Tetradentate Azolium Salts: Synthesis and Selective Recognition for Ions

Abstract: 2), were synthesized and characterized. Recognitions of 1 for anions and 2 for cations were studied through fluorescence spectra, UV/vis spectra, HRMS, 1 H NMR and infrared spectroscopies. The results revealed that 1 was able to differentiate 2 4 H POfrom other anions, and 2 was able to differentiate Ag + from other cations via fluorescence method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…66 Liu et al synthesized and characterized a tetradentate imidazolium salt 52 based on TPE (Scheme 8a) with multiple binding sites. 67 Compound 52 selectively recognized H 2 PO 4 − through the C–H⋯O hydrogen bond during the recognition process. The results indicated that compound 52 exhibited high sensitivity and selectivity for detecting H 2 PO 4 − .…”
Section: Tpe-based Macrocycles With Dual-ring Topologymentioning
confidence: 99%
“…66 Liu et al synthesized and characterized a tetradentate imidazolium salt 52 based on TPE (Scheme 8a) with multiple binding sites. 67 Compound 52 selectively recognized H 2 PO 4 − through the C–H⋯O hydrogen bond during the recognition process. The results indicated that compound 52 exhibited high sensitivity and selectivity for detecting H 2 PO 4 − .…”
Section: Tpe-based Macrocycles With Dual-ring Topologymentioning
confidence: 99%